COVID-19 Vaccination Status and Pregnancy Outcome during Third Wave - Madhusudan Dey; Shyamji Tiwari; Sunil Chawla; Pranjali Dhume; Abhijit Kumar; Priyanshi Chowdhary; Reshu Rawal (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Omicron was declared as a variant of concern by WHO on 26 Nov 2021. Omicron is highly transmissible, but the disease severity and morbidity were lesser compared to the Delta variant. However, COVID-19 Vaccine efficacy was reduced for the Omicron variant whereas it was highly efficacious for the Delta variant. Hence, for evidence-based counseling in pregnant patients about expected outcomes depending on their vaccination status, this prospective cohort study was conducted.